Statistical approach to modeling & optimization of surface roughness in high speed end milling of silicon with diamond coated tools - Amin, A. K. M. Nurul; Khalid, Noor Syairah; Mohd Nasir, Siti Nurshahida; Arif, Muammer Din (Trans Tech Publications, Switzerland, 2012)
This research demonstrated the use of conventional milling machines with diamond coated tools, high speed attachments, and air blowing mechanisms for ductile mode machining of silicon and subsequently modeling and optimizing the resultant surface roughness. Spindle speed, depth of cut, and feed rate, ranges: 60,000 to 80,000 rpm, 10 to 20 μm, and 5 to 15 mm/min respectively, were considered as the independent machining parameters for the modeling process. Compressed air at 0.35 MPa was also provided to prevent chip deposition on the finished surfaces. The resultant surfaces were analysed using Optical and Scanning Electron (SEM) Microscopes as well as Wyko NT 1100 and SurfTest SV-500 profilometers. The response, surface roughness, was then modeled using a small Central Composite Design (CCD) in Response Surface Methodology (RSM). The quadratic relation was found to be most suitable following Fit and Summary and ANOVA analyses. The relation was then optimized using Desirability Function (DF) in Design of Expert (DOE) software. The optimum attainable surface roughness, which was validated using experimental runs, was found to be 0.11 μm which may be considered quite satisfactory.